Pengaruh Pembelajaran Pendidikan Agama Islam (PAI) Terhadap Etika Digital Siswa SMA Boarding School (MBS) Muhiba Yogyakarta di Era Media Sosial - Falindri Prabastiwi; Tumin Tumin (Jayapangus Press, 2026)
The development of social media among high school students raises various digital ethical problems, such as cyberbullying, the spread of false information, the use of impolite language, and low responsibility in interacting online. This condition shows the importance of strengthening value-based education to form more ethical digital behavior. This study aims to analyze the influence of Islamic Religious Education (PAI) learning on students' digital ethics in the social media era. The research uses a quantitative approach with an ex post facto design carried out at SMA Boarding School (MBS) Muhiba Yogyakarta. The research sample amounted to 75 students who were selected through random sampling techniques. Data were collected using a Likert scale questionnaire that was tested for validity using Pearson Product Moment and reliability using Cronbach's Alpha (α > 0.70). Data analysis was carried out through descriptive statistics, normality test, linearity test, simple linear regression, and t test. The results of the study showed that PAI learning was in the good category, while students' digital ethics were in the good to very good category. The regression analysis produced a positive regression coefficient of 0.862 with a significance level of p < 0.001, which shows that PAI learning has a positive and significant effect on students' digital ethics. A correlation coefficient (R) value of 0.848 indicates a strong relationship between PAI learning and students' digital ethics, while a determination coefficient value (R²) of 0.719 indicates that PAI learning contributes 71.9% to the variation in students' digital ethics. The remaining 28.1% was influenced by factors other than the study. These findings show that PAI learning contributes significantly in supporting the formation of students' digital ethics in the social media era.